Hunting of Birds in the Dutch East Indies for the 19-20 Century Fashion Industry - Indira, Annajmia Sofi (Al-Isnad: Journal of Islamic Civilization History and Humanities, 2021)
The exploitation of the natural environment that occurred in the Dutch East Indies could not be separated from the influence of trade factors and the arrival of foreign nations. As happened to cloves in Maluku, nutmeg in Banda, sandalwood in Nusa Tenggara, teak in Java and birds of paradise in Irian. This hunt was influenced by the growth of the fashion industry in Europe and America which used fur as decoration on women's coats or hats at that time. The boom in demand for the feathers of these exotic birds reached its peak in the late 19th century. On the other hand, the concern about hunting, which is considered to be increasing over time, has caused reactions from various circles to produce several policies to suppress animal hunting that can lead to extinction.